Indice de pulsatilidad de la arteria umbilical como predictor de resultados adversos perinatales en embarazos de alto riesgo - Mariños Malón, ichael Kevyn (2022)
Ultrasound evaluation with Doppler technique of the umbilical vessels is a useful tool to estimate fetal well-being in high-risk pregnancies: preeclampsia and intrauterine growth restriction, for this reason the present research project aims to determine if the pulsatility index of The umbilical artery (IPAU) acts as a predictor of adverse perinatal outcomes in high-risk pregnancies, treated at the Belén de Trujillo hospital between January 2018 and January 2020. Due to the methodology, it is an observational, analytical case-control study. For the calculation of the sample, the epidat program was used with a result of 444, of which 148 are cases and 296 controls. The association between the altered pulsatility index (PI>P95) and adverse perinatal outcomes (APGAR < 7 at 5 min) will be determined by means of the "chi square" test and to calculate the strength of association the "odds" will be used. ratio” with a 95% confidence interval.